Direct Medical Costs of Epilepsy in Hospital III Miguel Grau of EsSalud (Peruvian Social Security) - Pérez Galdos, Proel (2010)
Objectives: To determine direct costs of epilepsy in a population assigned to one hospital in Peruvian Social Security (EsSalud) during year 2006. To point out which group of epileptic patients generate more direct costs. Methodology: A retrospective study including 462 epilepsy patients was performed in order to estimate medical direct costs, considering the Sales Value = Retail price – 19% (Peruvian added value tax), obtained from the EsSalud rate lists; as well as prices for antiepileptic drugs (AED) (generics), which are the lowest within Peru. Descriptive and analytic statistics were used, as well as Chi square and Students t tests.   Results: Fifty three per cent patients were male, and their average age was 40.7 years (± 22.03 SD); 95.7% of epileptic episodes were generalized crises, 17.7% were refractory, the average number of hospital visits was 6.26 (± 3.16 SD), 9.1% patients were hospitalized, and the average hospital stay was 6.93 days (± 4.72 SD). Annual direct costs were 71,433.24 US Dollars, average direct costs for controlled epilepsy were USD 118.5 and for refractory epilepsy, the amount was 321.9 USD (p<0.0001).   Conclusion: Costs for specialized consultations (37%) and AEDs (34%) represented the greatest annual expenses, and the direct average cost was 154.61 USD/patient/year. Average costs for refractory epilepsy were three times higher than those for controlled epilepsy; and direct costs reported in this study are quite lower than those reported in industrialized countries and even in neighboring countries.